Topographical alterations render bacterial biofilms susceptible to chemical and mechanical stress. (14th November 2018) - Falcón García, Carolina; Stangl, Felix; Götz, Alexandra; Zhao, Weining; Sieber, Stephan A.; Opitz, Madeleine; Lieleg, Oliver
Abstract : Treatment with concentrated ethanol, saline or glucose solutions smoothens biofilm surface topography and initially superhydrophobic/omniphobic biofilms are rendered hydrophilic. Abstract : For the inactivation or removal of bacterial biofilms via chemical or physical processes, it is crucial to sufficiently wet the biofilm surface. However, many bacterial biofilms efficiently resist wetting by water, oil or even organic solvents. Here, we demonstrate how exposing the surface of mature biofilm colonies to concentrated ethanol, saline or glucose solutions results in topographical changes that enable their wettability. With this approach, even omniphobic biofilm colonies become wettable towards aqueous solutions and oils. As a result of this reduced liquid repellency, the biofilms become susceptible to erosion by water which allows for their removal from the substrate they have been grown on. Moreover, bacteria within pre-treated biofilms can now be inactivated with antibiotic solutions. Thus, the biofilm treatment strategy presented here presents a new stepping stone for fighting biofilms in either industrial or medical settings.